Hardy and Fowles: on Problem of Perception of Victorian Tradition by Writer of 20th Century - E. S. Amineva (Научный диалог)
The article is devoted to the problem of the relationship between postmodernism and classical literature. The question is considered on the example of works by the Victorian writer who anticipated many of the trends of development of the English literature of 20th century. The article focuses on the works by Thomas Hardy. He was one of the first in the English literature of the 19th century who began to reflect on about tradition, turned to nature and unconscious in man. It is shown that the Victorian writer has created a gallery of characters, whose personal dilemmas are quite existential. It is noted that in the English classical tradition John Fowles is particularly attracted by the “crisis” authors, including Hardy. Special attention is paid to the influence of “historical” Hardy on the life and work of Fowles. The author dwells on the main stages of Fowles’ meeting with the life and work of a Victorian writer. The question is raised about the presence of Hardy’s intertext in the novel “Daniel Martin” on the plot, motif, imagery and spatial-temporal levels. The author notes that intertextual dialogue with Hardy in the works of Fowles is a special manifestation of intersubjectivity. It is concluded that among all Victorian writers, Hardy was “his own” for Fowles, however, the author of the 20th century rejects the gloom and despair of the writer of the 19th century.